The Relationship Between Environmental, Social and Governance (ESG) Disclosure and Financial Performance: Evidence from Thailand - Suttipun, Muttanachai; Yordudom, Thanyaorn; Khunkaew, Rojana (Journal of Environmental Accounting and Management, 2026)
The study aimed to investigate the level and pattern of environmental, social and governance (ESG) disclosure in annual report of listed companies in the Stock Exchange of Thailand (SET), and to examine the relationship between ESG disclosure and Thai corporate financial performance. The population was all listed companies in the SET. Using annual reports during 2015 to 2019, content analysis by word counting was used to quantify the level and pattern of ESG disclosure in corporate annual reports, while financial performance was measured by corporate net income. Descriptive analysis, independent sample t-test, correlation matrix, and panel data analysis were used to analyze the data of this study. The results found that there was an increase of ESG disclosure in annual reporting during 2015 to 2019 by listed companies in the SET. The most common ESG disclosure was governance information disclosure following by social and environmental information disclosures. Moreover, there was the significantly positive relationship between ESG disclosure and corporate financial performance. Using control variables, stock reaction, firm age, firm risk, and ESG group had a positive correlation with corporate financial performance. The Findings can demonstrate that stakeholder theory can be used to explain the benefit of ESG disclosure, although the disclosure is still voluntary reporting in Thailand.